Test Carbohydrate and Protein Content in Commercial Condensed Milk (SKM) Qualitative and Quantitative - Panjaitan, Riong Seulina; Christian, Yulius Evan; Wijaya, Bagas Eva; Andrian, Rahmat (Indonesian Journal of Pharmaceutical Research, 2023)
Sweetened condensed milk (SKM) is a milk product obtained by evaporating some of the water from pure milk with the addition of sugar. SKM is not a sterile product, but its preservation depends on the sugar content; (1) Background: Qualitative and quantitative tests of carbohydrates and proteins were carried out to determine the presence of carbohydrates and proteins in SKM. The qualitative test is based on a change in color or precipitate formed, while the quantitative test is to determine carbohydrate and protein levels; (2) Method: Qualitative and quantitative test of carbohydrates with the DNS method. Qualitative and quantitative test of protein with the Lowry method; (3) Results: Qualitative analysis of carbohydrates Molisch test on SKM "A", "B", "C", "D", "F" is positive, while SKM "E" is negative. The Osazon test on SKM "A", "B", "C", "D", "F" is positive and SKM "E" is negative. Iodine test, Benedict's test, Barfoed's test, Seliwanoff's test showed positive. Quantitative test for carbohydrates, sample concentration SKM "A" 0.228mg/mL the lowest value and SKM "F" 1.544mg/mL the highest value. Biuret test protein qualitative analysis on SKM "A", "B", "C" is positive while SKM "D", "E", "F" is negative. The Ninhydrin test on SKM "D", "F" is positive while SKM "A", "B", "C", "E" is negative. Sulfur test on SKM "A", "B" is positive while SKM "C", "D", "E", "F" is negative. Xantoprotein test on SKM "A", "C", "D", "E", "F" was positive while SKM "B" was negative. The Neuman test on SKM "D", "E", "F" is positive while SKM "A", "B", "C" is negative. Quantitative protein test for SKM“B” concentration was 10.77mg/mL, the lowest value, and the SKM “D” sample was 90.11mg/mL, the highest value; and (4) Conclusion: The qualitative analysis of carbohydrates SKM "A", "B", "C", "D", "F" showed positive and the quantitative test of SKM "F" contained high carbohydrates. Whereas SKM "A", "D", "F" showed positive protein and the SKM "D" quantitative test contained high protein.